2008
DOI: 10.1136/bjo.2007.127282
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Avastin for macular oedema secondary to retinal vein occlusion: a prospective study

Abstract: Licence for PublicationThe Corresponding Author has the right to grant on behalf of all authors and does grant on behalf of all authors, an exclusive licence (or non exclusive for government employees) on a worldwide basis to the BMJ Publishing Group Ltd to permit this article (if accepted) to be published in BJO and any other BMJPGL products and sublicences such use and exploit all subsidiary rights, as set out in our licence (http://bjo.bmj.com/ifora/licence.pdf).Competing Interest: None declared. BRVO) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
90
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(113 citation statements)
references
References 33 publications
17
90
1
5
Order By: Relevance
“…The side effects in terms of an elevation in intraocular pressure were present in the triamcinolone group only, in a similar frequency and amount as already reported for Caucasians and in another study on Chinese patients. [21][22][23][24][25] The finding of a discrepancy between a recurrence of macular oedema and continuously improved visual acuity agrees with an observation by Kriechbaum et al, 32 in which 3 months after the injection macular oedema recurred and visual acuity remained unchanged.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The side effects in terms of an elevation in intraocular pressure were present in the triamcinolone group only, in a similar frequency and amount as already reported for Caucasians and in another study on Chinese patients. [21][22][23][24][25] The finding of a discrepancy between a recurrence of macular oedema and continuously improved visual acuity agrees with an observation by Kriechbaum et al, 32 in which 3 months after the injection macular oedema recurred and visual acuity remained unchanged.…”
Section: Discussionsupporting
confidence: 90%
“…6,7,[9][10][11][12][13][14][15][16][17][18][19] The two major side effects of the intravitreal triamcinolone were a steroid induced increase in intraocular pressure and development of cataract. [21][22][23][24][25] In contrast, studies on intravitreal bevacizumab by Rosenfeld et al and other researchers showed an improvement in visual acuity, reduction in macular thickness, and only minor complications in patients with CRVOs, [26][27][28][29][30][31][32][33][34] so that intravitreal triamcinolone was rapidly exchanged by intravitreal bevacizumab for the treatment of CRVO. It agrees with this study, in which the best-corrected visual acuity improved significantly in the triamcinolone group and in the bevacizumab group with a no statistically significant difference in the gain in visual acuity between both study groups, although the reduction in macular oedema was slightly more pronounced in the triamcinolone group (Table 2) (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Kreichbaum et al have reported a decrease of central macular thickness from 558 m at baseline to 382 m at 6 months with 3, one monthly injection. 9 In our study we found a decrease in central macular thickness from a mean of 586.30 m at baseline to a mean of 329.10 m at approximately 12e16 weeks, i.e. after the third Anti-VEGF injection, which was again statistically significant ( p < 0.0001).…”
Section: Discussionsupporting
confidence: 62%
“…Kreutzer et al 8 reported improvement in visual acuity from 0.79 (0.39) log MAR to 0.51 (0.34) log MAR at 6 months ( p ¼ 0.009). Kreichbaum et al 9 reported an increase in BCVA from a mean of 20/100 at baseline to 20/50 at 6 months. In our study we observed an improvement in best corrected visual acuity from a mean of log MAR þ1.084 at baseline (Snellen's equivalent ¼ 5/60 approximately) to a mean of log MAR þ0.455 (Snellen's equivalent ¼ 6/18).…”
Section: Discussionmentioning
confidence: 99%